Psychological Problems among the Health Workers During Pandemic Covid-19 (Medico Legal Update, 2021)
The COVID-19 is a globally problem influences in all function of life, from health to economic and politicalof countries. It is still to elevated in incidence and killed people specially among health workers. The studyaimed to assess the psychological problems among health workers who work in health facilities at BabylonProvince.Descriptive-analytic study conducted during the era of COVI-19 by using online GHQ-12 items as instrumentto measure the symptoms of psychological problems. Convenience sample included 220 health workersparticipated in the study. The study revealed elevated in psychological problems among health workersand found significant relationship between gender and psychological problems. The study concluded to thesupport and available the enough training and medical health equipment may be reduced it.